Photo-excited dynamics in the excitonic insulator Ta2NiSe5. (5th July 2018) - Werdehausen, Daniel; Takayama, Tomohiro; Albrecht, Gelon; Lu, Yangfan; Takagi, Hidenori; Kaiser, Stefan
Abstract: The excitonic insulator is an intriguing correlated electron phase formed of condensed excitons. A promising candidate is the small band gap semiconductor Ta2 NiSe5 . Here we investigate the quasiparticle and coherent phonon dynamics in Ta2 NiSe5 in a time resolved pump probe experiment. Using the models originally developed by Kabanov et al for superconductors (Kabanov et al 1999 Phys. Rev . B59 1497), we show that the material's intrinsic gap can be described as almost temperature independent for temperatures up to about 250 K to 275 K. This behavior supports the existence of the excitonic insulator state in Ta2 NiSe5 . The onset of an additional temperature dependent component to the gap above these temperatures suggests that the material is located in the BEC-BCS crossover regime. Furthermore, we show that this state is very stable against strong photoexcitation, which reveals that the free charge carriers are unable to effectively screen the attractive Coulomb interaction between electrons and holes, likely due to the quasi 1D structure of Ta2 NiSe5 .